Monsters vs. aliens [videorecording (DVD)] - Letterman, Rob; Forbes, Maya; Wolodarsky, Wallace; Aibel, Jonathan, 1969-; Berger, Glenn (Universal Pictures Home Entertaintment, 2018)
Susan Murphy gets turned into a giant monster on her wedding day when a meteorite from outer space hits her. When she is taken to a secret government compound she meets up with a scruffy group of monsters who have also been sent to the compound over the years. A desperate order from the president will send the group of monsters into action to save the planet from aliens who are on a mission to destroy it.